Undifferentiated endometrial carcinomas show frequent loss of core switch/sucrose non-fermentable complex proteins - Köbel, Martin (Am J Surg Pathol, 2018)
Undifferentiated endometrial carcinoma is an aggressive type of endometrial carcinoma that typically presents with advanced stage disease and rapid clinical progression. In contrast to dedifferentiated endometrial carcinoma, undifferentiated carcinoma lacks a concurrent differentiated (typically low-grade endometrioid) carcinoma component, though the undifferentiated component of dedifferentiated carcinoma is similar histologically and immunophenotypically to pure undifferentiated carcinoma. We recently identified three mutually exclusive mechanisms of switch/sucrose non-fermentable (SWI/SNF) complex inactivation (BRG1 inactivation, INI1 inactivation or ARID1A/ARID1B co-inactivation) that are associated with histologic dedifferentiation in the majority of dedifferentiated endometrial carcinoma. In the current study, we aimed to determine by immunohistochemistry whether these patterns of SWI/SNF inactivation also occur in undifferentiated endometrial carcinomas. Of the 34 undifferentiated carcinomas examined, 17 (50%) exhibited SWI/SNF complex inactivation, with 11 tumors showing complete loss of both ARID1A and ARID1B, 5 showing complete loss of BRG1 and 1 showing complete loss of INI1. Ten of the remaining 17 undifferentiated carcinomas showed the following alterations: 5 tumors (15%) showed loss of ARID1A only with intact ARID1B, BRG1 and INI1 expression, 4 tumors (12%) showed mutated patterns of p53 staining with intact SWI/SNF protein expression, and 1 tumor (3%) harbored a POLE exonuclease domain mutation (P286R). SWI/SNF complex-inactivated tumors presented more frequently with extrauterine disease spread than those with intact expression (88% versus 41%, respectively). In addition, patients with SWI/SNF complex-inactivated tumors had a significantly worse disease-specific survival (p=0.02). The findings here demonstrate frequent SWI/SNF complex inactivation in undifferentiated endometrial carcinomas, which has future implications regarding therapies that target chromatin remodelling and epigenetic control.